2001
DOI: 10.1038/sj.bjp.0704018
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of sodium channel blocking and free radical scavenging activities into a single drug, AM‐36, results in profound inhibition of neuronal apoptosis

Abstract: 1 AM-36 is a novel neuroprotective agent incorporating both antioxidant and Na + channel blocking actions. In cerebral ischaemia, loss of cellular ion homeostasis due to Na + channel activation, together with increased reactive oxygen species (ROS) production, are thought to contribute to neuronal death. Since neuronal death in the penumbra of the ischaemic lesion is suggested to occur by apoptosis, we investigated the ability of AM-36, antioxidants and Na + channel antagonists to inhibit toxicity induced by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…This lazaroid compound is a potent antioxidant that inhibits lipid peroxidation in many models of oxidative stress. [33][34][35][36][37] Our data showed that U83836E significantly reduced hemoglobin neurotoxicity in a dose-dependent manner. Combination therapy using both U83836E and the broad-spectrum caspase inhibitor zVADfmk did not yield any additional protection.…”
Section: Discussionmentioning
confidence: 64%
“…This lazaroid compound is a potent antioxidant that inhibits lipid peroxidation in many models of oxidative stress. [33][34][35][36][37] Our data showed that U83836E significantly reduced hemoglobin neurotoxicity in a dose-dependent manner. Combination therapy using both U83836E and the broad-spectrum caspase inhibitor zVADfmk did not yield any additional protection.…”
Section: Discussionmentioning
confidence: 64%
“…Staurosporine is typically used as an apoptotic inducer. It has been shown to increase [Ca 2+ ] i and ROS, release of cytochrome c from mitochondria, and to activate caspases (7,21,34,48). In cortical neurons 3-AP, at 10 ìM for 24 h prior to and during the insult, reduced neurotoxicity of 1 ìM staurosporine by 47% (9).…”
Section: Pharmacology Neuroprotective Efficacy and Ec 50 Of 3-ap In Vmentioning
confidence: 99%
“…Therefore, in recent years synthetic and natural antioxidants have gained tremendous interest because of their potential use as neuroprotective compounds in the clinic (Callaway et al, 2001;Herin et al, 2001;Mackensen et al, 2001). Antioxidants were found to decrease reactive oxygen species-induced brain damage produced in different experimental models, as well as after ischemic insults (Uyama et al, 1990;Clements et al, 1993;Watanabe et al, 1994).…”
mentioning
confidence: 97%